Post-communist party systems competition, representation, and inter-party cooperation - Kitschelt, Herbert 1955- (Cambridge University Press, 1999)
Post-Communist Party Systems examines democratic party competition in four post-communist polities in the mid-1990s: Bulgaria, the Czech Republic, Hungary, and Poland. Legacies of pre-communist rule turn out to play as much a role in accounting for differences as the institutional differences incorporated in the new democratic rules of the game. The book demonstrates various developments within the four countries with regard to different voter appeal of parties, patterns of voter representation, and dispositions to join other parties in legislative or executive alliances. The authors also present interesting avenues of comparison for broader sets of countries
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Politik; Political parties / Europe, Eastern; Post-communism / Europe, Eastern; Parteienwettbewerb; Parteiensystem; Europe, Eastern / Politics and government / 1989-; Osteuropa